PELAKSANAAN PERATURAN MENTERI HUKUM DAN HAK AZASI MANUSIA REPUBLIK INDONESIA NOMOR 17 TAHUN 2018 TENTANG PENDAFTARAN PERSEKUTUAN KOMANDITER, PERSEKUTUAN FIRMA, DAN PERSEKUTUAN PERDATA DI LEMBAGA KEUANGAN - Erlistya Faranti (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT   Registration of limited partnership, firm association, and civil partnership is regulated in the Commercial Code Article 23 which states that "Firm Persero is required to register the deed in the register provided for that at the clerk of raad van justitie (District Court)". and Civil Associations. This regulation uses the Lex Posterior Derogat Legi Priori Principle where the new Law (Lex Posterior) overrides the old Law (Legi Priori).This type of research is used in this research is juridical normative, which is research that examines the study of documents that use various primary legal materials such as regulations.Registration of Non-Legal Entity Business Entities based on the Regulation of the Minister of Law and Human Rights Number 17 of 2018 is carried out online through the Business Entity Administration System in General Law Administration. The impact on financial institutions to check the licensing of Business Entities through the validation Sheet from The Ministry of Law and Human Rights .Regulation of the Minister of Law and Human Rights Number 17 of 2018 Registration of Non-Legal Entities uses the services of a notary to carry out their registration. The impact on financial institutions is that financial institutions will find it easier to check permits related to business entities that have been given financing by banks and the distribution of funds will be easier because they have been registered with the Ministry of Law and Human Rights. Keywords : Implementation Regulation of the Minister of Law and Human Rights Number 17 of 2018.